Impact of demographic change on pension scheme financing in the Caribbean - Jordan, Alwyn (2000)
Utilizes a simple social security projection model to analyse the implications of population aging on financing social security pensions in the long-term. Examines four Caribbean nations namely Barbados, St. Lucia, Jamaica and Trinidad and Tobago. Investigates a number of reform strategies which would enhance the sustainability of the nation's social security programmes.